Visual Vertigo, Phantasmagoric Physiognomies: Joseph Roth and Walter Benjamin on the Visual Experience of Architecture - Stefan Koller (Footprint)
This paper scrutinises Benjamin’s interest in the urban fabric of nineteenth century Paris, and compares it to contemporary writings on Paris and on (more generally) new forms of urbanism in the journalistic work of Joseph Roth. It argues that both authors come to terms with the modern city through a shared set of observations and concepts, particularly the concepts of ‘expressionism’, ‘physiognomy’, and ‘phantasmagoria’. The paper clarifies how Roth and other writers in (or immediately before) the 1920s developed such concepts, and how Benjamin’s The Arcades Project builds on these writers. It shows that Benjamin’s specific contribution to this body of literature is the invention of a secular mythology, with a clear application to architecture in Benjamin’s focus on the ‘boundless interiorisation’ of glass and iron construction. The paper concludes that Benjamin’s contribution to architecture is considerable when compared to the materialist orientation of his main sources in The Arcades Project (especially Boetticher and Giedion), but that the purported improvements on Benjamin’s distinguished predecessors of architectural non-materialism are by comparison less impressive.